2001
DOI: 10.4269/ajtmh.2001.65.614
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to anemia after uncomplicated falciparum malaria.

Abstract: Abstract. The factors contributing to anemia in falciparum malaria were characterized in 4,007 prospectively studied patients on the western border of Thailand. Of these, 727 patients (18%) presented with anemia (haematocrit Ͻ 30%), and 1% (55 of 5,253) required blood transfusion. The following were found to be independent risk factors for anemia at admission: age Ͻ 5 years, a palpable spleen, a palpable liver, recrudescent infections, being female, a prolonged history of illness (Ͼ 2 days) before admission, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
329
6
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(374 citation statements)
references
References 33 publications
(45 reference statements)
37
329
6
2
Order By: Relevance
“…14 The causative role of malaria, particularly Plasmodium falciparum, in anemia is particularly important in malariaendemic regions, including much of sub-Saharan Africa (SSA). [15][16][17][18] The vast majority of people living in Uganda are at risk of malaria, and although malaria transmission is of varied intensity, as documented by the entomological inoculation rate, rates of malaria transmission in Uganda are among the highest in the world. 19 According to the WHO, 90% of the total Ugandan population reside in areas of high malaria transmission, almost exclusively via P. falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…14 The causative role of malaria, particularly Plasmodium falciparum, in anemia is particularly important in malariaendemic regions, including much of sub-Saharan Africa (SSA). [15][16][17][18] The vast majority of people living in Uganda are at risk of malaria, and although malaria transmission is of varied intensity, as documented by the entomological inoculation rate, rates of malaria transmission in Uganda are among the highest in the world. 19 According to the WHO, 90% of the total Ugandan population reside in areas of high malaria transmission, almost exclusively via P. falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…There are potential applications of our findings: In addition to other causes, anemia in falciparum malaria is related to antimalarial drug resistance and treatment failure [26]. Therefore, prompt treatment of acute malaria infections with effective non-anemia and non-gametocytaemia-inducing drugs such as the artemisinin derivatives [19,22,29,30] should reduce the burden of malarial anemia; community control of infections and anemia should reduce the risk of gametocyte carriage and a male biased PfGSR and burden of malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In natural infections in animals sex ratio often increase over the course of infections [12,25]. Since a longer duration of illness is a predictor of anemia in malaria [26], it would appear the relatively longer duration of the untreated infections in anemic children allow a faster progression of a natural change of increase in PfGSR. The lack of correlation between hematocrit and PfGSR in anemic children and the significantly negative correlation in the non-anemic children, Mean gametocyte sex ratio suggest that, in this cohort of children, the critical haematocrit threshold producing 'all or none effect' on GSR was a value below 25%.…”
Section: Discussionmentioning
confidence: 99%
“…In uncomplicated malaria, the hemoglobin nadir is usually around 1 week after treatment initiation with a rapid recovery to normal over the subsequent 3-4 weeks. 19 In our first patient, hospital discharge was delayed since the concept PADH was not recognized and the patient underwent invasive procedures in an attempt to explain his anemia. Previously, it was suggested that the absence of cases of PADH reported from North America might be explained by the differences between the artesunate products used in North America and Europe.…”
Section: Discussionmentioning
confidence: 99%